Behavior of Plant Parasitic Nematodes Associated With Mulberry Plants with Special Emphasis to the Family Hoplolaimidae from Manipur, India - Bina, Loukrakpam; Mohilal, Naorem (International Journal of Scientific Research in Biological Sciences, 2020)
A study for the population behavior of plant parasitic nematodes associated with mulberry plants was conducted as a part of a thesis submitted to Manipur University in four mulberry farms located at valley districts of Manipur, India. Out of the parasitic nematodes, tylenchid nematodes belonging to the family Hoplolaimidae were found abundantly from the all studied farms. Population changes of the nematodes in relation to soil pH, organic carbon, nitrogen, phosphorous and potassium contents were found. The study showed increased nematode population with increased in soil organic carbon, nitrogen, phosphorous and pH contents and decreased population with increased soil potassium content. Highest nematode population was found at clayey- loam soil type with greater contents of nitrogen, phosphorous, potassium and pH whereas least population was found at sandy loam soil with least nitrogen and phosphorous contents. Among the nematode species of the family Hoplolaimidae, the most abundant Helicotylenchus graminophilus increased its population with increase in soil organic carbon, nitrogen, phosphorous and pH contents while the population decreased with increased soil potassium content. The least abundant nematode population of Rotylenchus minutus increased with increased of potassium content while its population decreased with increased in soil pH, organic carbon, nitrogen and phosphorous contents